Taxonomic updates for diurnal velvet ants (Hymenoptera: Mutillidae) in the United States of America - Williams, Kevin A. (Zootaxa, 2023)
This paper provides miscellaneous taxonomic updates for diurnal velvet ants in the USA. Six valid species of Dasymutilla Ashmead, 1899, one valid species of Ephuta Say, 1836 and six valid species of Pseudomethoca Ashmead, 1896 are regarded. Two new species are described: Pseudomethoca peremptrix sp. nov. and P. sonorae sp. nov. The female formerly associated with Dasymutilla zelaya (Blake, 1871) is recognized as a color variant of D. vestita (Lepeletier, 1845). Sixteen new synonymies are proposed: Dasymutilla chisos Mickel, 1928, syn. nov. under D. gloriosa (Saussure, 1868); D. cotulla Mickel, 1928, syn. nov., D. homole Mickel, 1928, syn. nov. and D. vandala Mickel, 1928, syn. nov. under D. vestita (Lepeletier, 1845); D. dorippa Mickel, 1928, syn. nov. under D. flammifera Mickel, 1928; D. ocydrome Mickel, 1928, syn. nov. under D. connectens (Cameron, 1895); Mutilla phaon Fox, 1899, syn. nov. under D. pseudopappus (Cockerell, 1895); M. zelaya Blake, 1871, syn. nov. under D. gorgon (Blake, 1871); Ephuta tentativa Schuster, 1951, syn. nov. under E. scrupea Say, 1836; P. dentifrontalis Bradley in Mickel, 1924, syn. nov. under P. athamas (Fox, 1899); P. albicoma Mickel, 1924, syn. nov., P. contumeliosa Mickel, 1935, syn. nov., P. manca Mickel, 1924, syn. nov. and P. oculissima Mickel, 1924, syn. nov. under P. contumax (Cresson, 1865); M. aeetis Fox, 1899, syn. nov. under P. sanbornii (Blake, 1871); and P. (Nomiaephagus) vanduzei Bradley, 1916, syn. nov. under P. wickhami (Cockerell & Casad, 1895).